The Term Structure as a Predictor of Real Economic Activity - Estrella, Arturo; Hardouvelis, Gikas A. (Journal of Finance, 1991)
A positive slope of the yield curve is associated with a future increase in real economic activity: consumption (nondurables plus services), consumer durables, and investment. It has extra predictive power over the index of leading indicators, real short-term interest rates, lagged growth in economic activity, and lagged rates of inflation. It outperforms survey forecasts, both in-sample and out-of-sample. Historically, the information in the slope reflected, inter alia, factors that were independent of monetary policy, and thus the slope could have provided useful information both to private investors and to policy makers. THE FLATTENING OF THE yield curve in 1988 and its inversion in early 1989 have been interpreted by many business economists and financial analysts as evidence that a recession is imminent. Implicit in this interpretation is the presumption that a flattening of the yield curve predicts a drop in future spot interest rates and that these lower rates are associated with a lower level of real GNP. Recent empirical work on the term structure of interest rates confirms that changes in the slope of the yield curve predict the correct direction of future changes in spot rates, yet there is little empirical work on the predictability of changes in real economic activity.1 Indeed, given the near-random-walk empirical behavior of real GNP, a finding that the yield curve can predict future changes in real output would be very impressive.2 Predictability of changes in real output is associated with other equally important questions: How much extra information is there in the term